P251 Antiphospholipid antibodies in Crohn's disease: Results of a prospective single-center study. (27th May 2021) - Serghini, M; Ben Youssef, H; Baccouche, H; Hafi, M; Labidy, A; Ben Mustapha, N; Fekih, M; Boubaker, J
Abstract: Background: Assess the prevalence of antiphospholipid antibodies (APL) and their association with disease phenotype and activity in patients with Crohn disease (CD). Methods: This is a prospective study involving 30 patients with CD over a period of 2016 to 2020. Family and personal history of thromboembolic disease and fetal loss as well as their delay in relation to the date of the sample were taken from from the interrogation. Disease-related data such as age at the time of diagnosis, location and phenotype of the disease as well as treatment medical received were identified from the medical records. Disease activity was evaluated according to the CDAI (Crohn Disease Activity Index) score calculated time of inclusion. The serum of the patients was tested on anti-β2-glycoprotein-I (anti-β2-GPI Ig M / G), anti-cardiolipin (ACA Ig M / G) by method enzyme immunoassay (ELISA). This test was considered positive if the rate of anti-cardiolipin antibody was> 12U / mL and the level of anti-β2- glycoprotein-1> 8U / mL. The occurrence of thromboembolic events was noted during follow-up. Results: The average age was 47.3 ± 10.8 years (29 men and 21 women). A family history of thromboembolic disease has been noted in 2 patients. A patient developed a pulmonary embolism 37 months before his inclusion in postoperative context. A history of fetal loss was reported in 7 women (16%) with a delay ranging from 5 to 432 months (in mean 181.6 ± 146) before their inclusion in the study. The average age at time of diagnosis was 37.9 ± 11.7 years. Colonic localization of the disease was noted in 12 patients (41.4%) and the inflammatory phenotype was the more common (62.1%). The disease was active in 13 patients (44.8%) with a mean CDAI score of 149.2 ± 111.7 (23–469). A patient has presented a mesenteric infarction during his follow-up 35 months after his inclusion. Positive anti-β2-glycoprotein-1 antibody levels IgG type with levels negative anti-cardiolipin antibodies were found in 2 patients (6%). No patient had positive anti-cardiolipin antibodies. No difference was found for the prevalence of anti-β2-GPI in patients patients in remission compared to those with active disease (p = 0.22) and in patients with severe acute colitis compared to the rest of the patients (p = 0.2). The frequency of β2-GP1 was not higher in patients with CRP greater than 6 mg / L compared to those with a normal CRP (p = 0.4). Anti-TNF treatment was started in 5 patients and no association was found between anti-TNF treatment and the prevalence of anti-β2-GP1 (p = 0.7). APL status was not associated with phenotype and localization of disease or thrombotic events. Conclusion: The present study did not demonstrate an association between APL antibodies and disease phenotype or activity.